Positive Selection Drives Evolution at the Host–Filovirus Interaction Surface. (10th August 2016) - Pontremoli, Chiara; Forni, Diego; Cagliani, Rachele; Filippi, Giulia; De Gioia, Luca; Pozzoli, Uberto; Clerici, Mario; Sironi, Manuela
Abstract: Filovirus infection is mediated by engagement of the surface-exposed glycoprotein (GP) by its cellular receptor, NPC1 (Niemann-Pick C1). Two loops in the C domain of NPC1 (NPC1-C) bind filovirus GP. Herein, we show that filovirus GP and NPC1-C evolve under mutual selective pressure. Analysis of a large mammalian phylogeny indicated that strong functional/structural constraints limit the NPC1 sequence space available for adaptive change and most sites at the contact interface with GP are under negative selection. These constraints notwithstanding, we detected positive selection at NPC1-C in all mammalian orders, from Primates to Xenarthra. Different codons evolved adaptively in distinct mammals, and most selected sites are located within the two NPC1-C loops that engage GP, or at their anchor points. In Homininae, NPC1-C was a preferential selection target, and the T419I variant possibly represents a human-specific adaptation to filovirus infection. On the other side of the arms-race, GP evolved adaptively during filovirus speciation. One of the selected sites (S142Q) establishes several atom-to-atom contacts with NPC1-C. Additional selected sites are located within epitopes recognized by neutralizing antibodies, including the 14G7 epitope, where sites selected during the recent EBOV epidemic also map. Finally, pairs of co-evolving sites in Marburgviruses and Ebolaviruses were found to involve antigenic determinants. These findings suggest that the host humoral immune response was a major selective pressure during filovirus speciation. The S142Q variant may contribute to determine Ebolavirus host range in the wild. If this were the case, EBOV/BDBV (S142) and SUDV (Q142) may not share the same reservoir(s).